PERENCANAAN DRAINASE JALAN RAYA SEMARANG - BAWEN KM 12+400 - KM 16+600 (JAMU JAGO - BALAI PELATIHAN TRANSMIGRASI DAN PENYANDANG CACAT JATENG) - Yohanna Fabiola Pane; Firman Hasiholan; Sri Sangkawati; Pranoto Samto Atmojo (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Flooding or inundation problem is often occurs in highways in Indonesia, including in Semarang - Bawen highway which national highway. When raining, inundation occurs along that highway, so disturbs people and causes damage to pavement. Inundation occurs due to the not optimum drainage system cause of sedimentation at curb inlet and side channel. So, to find out how the drainage system performance we do hydrological analysis to calculate discharge plan with a return period of 5 years according to total area of drainage channel and city typology and then compare it with existing discharge side channel and culvert. Results of the comparison between discharge plan and existing discharge show that existing side channel and culvert can not accomodate discharge plan, so it is necessary to redimensional side channel and culvert. Cross section is planned rectangular because the limited area, while culverts is planned circle and rectangular (U-ditch). Curb inlet is planned 2 types namely (1) curb with hole with dimension 13/16 x 30 x 50 cm and its hole 15 x 30 cm to slope < 6% and concrete curb inlet with dimension 10 x 15 to slope ≥ 6%.